The Spread of COVID-19 and Policy Responses - Islamaj, Ergys (World Bank, Washington, DC, 2021)
Since early 2020, the COVID-19 (coronavirus) pandemic has spread to most countries and territories around the world. For many countries, the second wave of infections is turning out to be more serious than the first. Notwithstanding the global spread of the virus, public policy responses have varied across countries and regions. This brief analyzes the spread of COVID-19 and the effectiveness of policy efforts to contain the disease across a large number of countries. The findings suggest that public health measures - especially testing - and economic support policies are associated with effective containment of the disease, and thus are supporting fundamental prerequisites for a resumption of normalcy. This brief examines the evolution of COVID-19 and public policy responses across country groups around the world; presents an econometric analysis of the relationship between the spread of infections and the policy responses; and concludes with main policy implications.